Konsep Penilaian Hasil Belajar Perenialisme dan Implementasinya di Madrasah - Nasir, Muhammad (IAIN Samarinda, 2010)
There is a tendency of some communities in Indonesia has always made the learning outcomes in the form of the final value to measure educational success, even being the only measure used to jasticed intelligence of a learner. Children who are considered smart and smart is just a child or children who have ranked highest. While children who have a low value is considered not successful and failed in learning. In this case, some of our communities less attention to aspects of children's behavior in the form of the attitude of honesty, hard work, creativity, independence, thinking skills and responsibilities and others. Noting the tendency of some communities, the authors saw that the assessment perenialisme still a dominant aspect in the assessment at the schools, including madrasah. This paper attempts to explore how the concept of assessment of learning outcomes perenialisme in madrasah, which is presented by first seeing perenialisme as one of the schools of philosophy of education. Next in succession, the flow is presented that supports education, orientation and model concepts relevant curriculum, policies and implementation of assessment in Madrasah